2016
DOI: 10.3390/ijms17101597
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-Related Gene Polymorphisms, Plasma 25-Hydroxy-Vitamin D, Cigarette Smoke and Non-Small Cell Lung Cancer (NSCLC) Risk

Abstract: Epidemiological studies regarding the relationship between vitamin D, genetic polymorphisms in the vitamin D metabolism, cigarette smoke and non-small cell lung cancer (NSCLC) risk have not been investigated comprehensively. To search for additional evidence, the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique and radioimmunoassay method were utilized to evaluate 5 single-nucleotide polymorphisms (SNPs) in vitamin D receptor (VDR), 6 SNPs in 24-hydroxylase (CYP24A1), 2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 78 publications
2
47
0
Order By: Relevance
“…The two polymorphisms rs10877012 and rs3782130 did not increase the risk of developing this type of cancer. When smokers and non-smokers were compared between themselves, correlating these polymorphisms with the plasma concentration of 25(OH)D did not show any statistical significance [112]. This is consistent with another GWAS, where there was no association between polymorphism in CYP27B1 and level of 25(OH)D [39].…”
Section: Lung Cancersupporting
confidence: 84%
“…The two polymorphisms rs10877012 and rs3782130 did not increase the risk of developing this type of cancer. When smokers and non-smokers were compared between themselves, correlating these polymorphisms with the plasma concentration of 25(OH)D did not show any statistical significance [112]. This is consistent with another GWAS, where there was no association between polymorphism in CYP27B1 and level of 25(OH)D [39].…”
Section: Lung Cancersupporting
confidence: 84%
“…In the second meta‐analysis, Zhang et al observed an RR of 0.83 (95% CI, 0.77–0.90) comparing lowest to highest 25(OH)D levels 43 . Based on circulating 25(OH)D levels, poorer survival and an increased risk for cancer recurrence have been reported by some investigators, while other studies have found no association 44 48 …”
Section: Vitamin Dmentioning
confidence: 98%
“…A casecontrol study including 426 patients with non-small cell lung cancer (NSCLC) and 445 controls from China studying VDR polymorphisms rs1544410 and rs731236 found a statistically significant relation between VDR polymorphism and reduction in NSCLC risk (82). Furthermore, the association of increased VDR mRNA expression with worse prognostic factors in papillary thyroid carcinoma suggests the role of VDR in thyroid cancer (83).…”
Section: Additional Cancer-related Interactions Of Vdr Polymorphismsmentioning
confidence: 99%